Pandemics and the future of human-landscape interactions. (September 2020) - Chin, Anne; Simon, Gregory L.; Anthamatten, Peter; Kelsey, Katharine C.; Crawford, Benjamin R.; Weaver, Amanda J.
Abstract: Pandemics have accelerated in frequency in recent decades, with COVID-19 the latest to join the list. Emerging in late 2019 in Wuhan, China, the virus has spread quickly through the world, affecting billions of people through quarantine, and at the same time claiming more than 800, 000 lives worldwide. While early reflections from the academic community have tended to target the microbiology, medicine, and animal science communities, this article articulates a viewpoint from a perspective of human interactions with Earth systems. We highlight the link between rising pandemics and accelerating global human impacts on Earth, thereby suggesting that pandemics may be an emerging element of the "Anthropocene." Examples from Denver, Colorado, USA, show how policy responses to the COVID-19 pandemic changed human-environment interactions and created anomalous landscapes at the local scale, in relation to the quality of air and patterns of acquiring and consuming food. In recognizing the significance of novel infectious diseases as part of understanding human-landscape interactions in the Anthropocene, as well as the multi-scale interconnectedness between environment and health, this viewpoint converges toward an urgent need for new paradigms for research and teaching. The program required extends well beyond the already broad interdisciplinary scholarship essential for addressing human-landscape interactions, by integrating the work of health scientists, disease specialists, immunologists, virologists, veterinarians, behavioral scientists, and health policy experts.